2007
DOI: 10.1124/jpet.107.121756
|View full text |Cite
|
Sign up to set email alerts
|

Neuronally Released Acetylcholine Acts on the M2 Muscarinic Receptor to Oppose the Relaxant Effect of Isoproterenol on Cholinergic Contractions in Mouse Urinary Bladder

Abstract: We investigated whether M(2) muscarinic receptor activation opposes isoproterenol-induced relaxation in mouse urinary bladder and whether endogenous acetylcholine acts through a similar M(2) mechanism. When measured in urinary bladder from M(3) receptor knockout mice, the muscarinic agonist oxotremorine-M elicited only very weak contractions. In the presence of alpha,beta-methylene ATP (30 microM) and isoproterenol (1 microM), however, oxotremorine-M elicited a robust contractile response. This response was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
3
26
0
2
Order By: Relevance
“…Isoproterenol was slightly more effective in relaxing EFS contractions in M 2 KO bladder compared with wild-type tissue (Fig. 6a), indicating that neuronally released acetylcholine acts on the M 2 receptor to oppose relaxant responses, as described previously, with other stimulation parameters (Ehlert et al, 2007). STZ treatment enhanced this effect (Fig.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Isoproterenol was slightly more effective in relaxing EFS contractions in M 2 KO bladder compared with wild-type tissue (Fig. 6a), indicating that neuronally released acetylcholine acts on the M 2 receptor to oppose relaxant responses, as described previously, with other stimulation parameters (Ehlert et al, 2007). STZ treatment enhanced this effect (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…It seems likely that the loss of function can be attributed to the loss of M 2 receptors, as described above, and not to changes in other mechanisms. We have previously reported no change in the sensitivity of the M 2 KO mouse urinary bladder to the contractile effects of mATP and prostaglandin F 2␣ and the relaxant effect of isoproterenol against KCl-and mATP-induced contractions (Ehlert et al, 2005(Ehlert et al, , 2007. Ito et al (2009) reported 35 and 34% decreases in total muscarinic receptors in bladder from M 4 and M 5 KO mice, suggesting that a loss of one subtype in a single KO mouse causes a loss of other subtypes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a broader sense, such studies are a reminder that life-long knockout of one gene can lack expected or have unexpected consequences due to cross-regulation. On the other hand, studies based on systemic knockout mice, e.g., for the M 2 receptor (Ehlert et al 2007) and studies based on highly M 2 selective antagonists (Witte et al 2011) have yielded consistent findings on the interaction between the muscarinic and the β-adrenoceptor system, e.g., in the urinary bladder.…”
mentioning
confidence: 92%